Influence of palatoplasty on occlusion of patients with isolated cleft palate - Omar Gabriel da Silva Filho; Elisa Teixeira Marinho; Rita de Cássia Moura Carvalho Lauris (Dental Press Editora, 2012)
OBJECTIVE: This study compared the dental arch morphology of adult patients with isolated cleft palate in order to verify the influence of palatoplasty on occlusion. METHODS: Cast models of 77 patients, 30 males and 47 females, with an average age of 21 years and no syndromes were taken. They were in the permanent dentition and had not undergone orthodontic treatment. The sample was divided into non-operated and operated patients, the latter having been submitted to palatoplasty at a mean age of 2.2 years. RESULTS: Almost 80% of the sample exhibited sagittal discrepancies in the inter-arch relationship, with a Class II malocclusion prevailing (59.74%) followed by Class III (20,78%), regardless of palatoplasty. Transverse analysis showed a 23% incidence of posterior crossbite also not influenced by palatoplasty. Intra-arch relationship indicated that constriction and crowding on the upper arch were more frequent in the operated group (p=0.0238 and p=0.0002, respectively), showing an influence of palatoplasty on its morphology. The predominant morphological characteristics in patients with isolated cleft palate were a Class II malocclusion, upper dental arch constriction and upper and lower anterior crowding. CONCLUSION: The influence of palatoplasty was restricted to constriction and crowding of the upper dental arch, with no interference from the extension of the cleft, except for the upper crowding, which occurred more in patients with complete cleft palates.